Radiology of the liver, biliary tract, and pancreas - Friedman, Arnold C; Dachman, Abraham H (Mosby, 1994)
This book concentrates on the accessory organs of the alimentary system: the liver, biliary tract, and pancreas, and covers them in depth, with an approach that integrates clinical presentation with radiologic and gross pathologic appearance. The images are state-of-the-art and include all relevant imaging methods, as well as gross pathologic specimens, and anatomical line drawings. Reference lists are divided by topic for ease of use.
Keywords: Bile Duct Diseases; nemoci žlučových cest; nemoci jater; Liver Diseases; gastroenterologie; Pancreatic Diseases; diagnostické zobrazování; Diagnostic Imaging; radiologie, nukleární medicína a zobrazovací metody; nemoci slinivky břišní; chemie, klinická chemie